Kombucha Tea Production Using Different Tea Raw Materials - Putri Ardila Sari; Irdawati Irdawati (Bioscience, 2019)
Tea (Camellia sinensis) is an agricultural product that is widely issued by people around the world. Some types of tea in the world are green tea, black tea, oolong tea and white tea. Kombucha tea is brewed water for tea and sugar then given bacteria and fungi and fermented for 7-10 days. The purpose of this study was to determine the quality of kombucha of several different types and determine the organoleptic value of fermented kombucha tea using different types. This research was conducted in April-July 2019 in the Microbiology Laboratory of the Department of Biology FMIPA Padang State University. This research is an experimental study with 5 treatments and 1 repetition (K: kombucha starter, P1: kombucha starter + green tea, P2: kombucha starter + black tea, P3: kombucha starter + oolong tea, P4: kombucha starter + white tea. Parameters Calculated are the number of microbes, nata thickness, pH of kombucha tea, total acetic acid, and organoleptic tests of kombucha tea.The results of this study indicate differences in the types of tea used in kombucha fermentation, the quality of kombucha tea produced, kombucha tea using black tea. The organoleptic test requested by the panelists was kombucha tea from white tea.